2020
DOI: 10.1380/ejssnt.2020.275
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Control of Aluminum Oxide Thin Films Formed on Surfaces of FeCo-V Alloys

Abstract: X-ray photoelectron spectroscopy (XPS), ellipsometry, and cathode luminescence were utilized for characterizing oxide films formed on the surfaces of FeCo-V alloys (Permendur) that contained small amounts of aluminum via annealing under a low partial pressure of oxygen. XPS spectra showed that the oxide films were composed primarily of aluminum oxide, which was a result of preferential oxidation of aluminum on the surfaces of the alloys during annealing. The thicknesses of the oxide films were estimated from X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Figure 2 shows the thickness of the aluminum oxide films on the FeCo-V alloys, with Al mass % of 0.25, 0.50, and 0.75, measured by ellipsometry. In a previous study [10], non-destructive ellipsometry provided reasonable results rather than sputtered depth profiles; the thickness of those samples annealed for 1173 K for 0.5 h are also shown in Figure 2. The thickness of the aluminum oxide thin films increased with increasing the aluminum content in the alloys, annealing temperature, and annealing time.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Figure 2 shows the thickness of the aluminum oxide films on the FeCo-V alloys, with Al mass % of 0.25, 0.50, and 0.75, measured by ellipsometry. In a previous study [10], non-destructive ellipsometry provided reasonable results rather than sputtered depth profiles; the thickness of those samples annealed for 1173 K for 0.5 h are also shown in Figure 2. The thickness of the aluminum oxide thin films increased with increasing the aluminum content in the alloys, annealing temperature, and annealing time.…”
Section: Resultsmentioning
confidence: 63%
“…These results indicate that aluminum, one of the less noble elements, is preferentially oxidized in the Fe-based alloy, containing such elements annealed under a low partial pressure of oxygen. This annealing process is effective for fabricating aluminum oxide thin films on the surface of the FeCo-V alloys, as bulk aluminum oxide is fundamentally insulated [10]. To understand the formation conditions of aluminum oxide thin films, the mechanism of the oxide film formation has been discussed based on the thermodynamic properties of the relevant elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of Al 2 O 3 in iron-based alloys and heatresistant steels has also been investigated. [10][11][12][13][14][15][16][17][18][19] It is often necessary to understand and analyze the structural changes of Al 2 O 3 on the surfaces of iron-based alloys at high tem-peratures because of the practical applications of these alloys. For example, X-ray diffraction, which is practically applied to on-line analysis of galvannealed coating layers, 20) would be applicable to the on-site identification of a specific structural isomer of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that the oxidation of a less-noble metal (such as aluminum) at high temperatures often results in the formation of a non-conductive thin layer on alloy surfaces under controlled annealing. 19) In this study, X-ray photoelectron spectroscopy (XPS) and ellipsometry were used to investigate the growth of Al 2 O 3 thin layers on Fe-based alloys. The results show that ~100 nm thick Al 2 O 3 layers are formed on the surface of the samples after annealing at high temperatures and under oxygen at low partial pressure.…”
Section: Introductionmentioning
confidence: 99%